Analisa Stabilitas Lereng di Area Bendungan Kerinci, PLTA Merangin, Kecamatan Merangin, Kabupaten Kerinci, Provinsi Jambi - I Putu Audiantafika; Hurien Helmi; Obrin Trianda (ReTII, 2023)
This study aims to evaluate the geological conditions of the research area and the geological potential it contains. The limit equilibrium analysis of PT Kerinci Merangin Hidro indicates that the slope is in a safe condition, with safety factors obtained from the GLE/Morgenstern method at 1.8, from the Spencer method at 1.9, and from the Bishop Simplified method at 1.9. The installation of rock bolts with a spacing of 3.5 meters between each bolt has reached the standard point, considering the lithological conditions. However, the rock bolt installation has not penetrated the sliding surface. The safety factor without rock bolts obtained from the finite element analysis is 1.3. Although the factor of safety has reached a safe point, the addition of reinforcement needs to be considered by analyzing the sliding surface using the finite element method, taking into account the largest total displacement. Based on the interpretation results with an average depth of approximately 10-11 meters from the slope surface, a rock bolt length of about 13-14 meters is required. The lithology that needs attention in the right bank area is lapilli lithology with a rock class of low (CL)." Note: This abstract is a concise summary of the research provided. For any specific purposes or further inquiries about this research, it is essential to refer to the original research document to gain a more in-depth understanding.